Spatial and temporal patterns of Holocene precipitation change in the Iberian Peninsula. (15th February 2022) - Ilvonen, Liisa; López‐Sáez, José Antonio; Holmström, Lasse; Alba‐Sánchez, Francisca; Pérez‐Díaz, Sebastián; Carrión, José S.; Ramos‐Román, María J.; Camuera, Jon; Jiménez‐Moreno, Gonzalo; Ruha, Leena; Seppä, Heikki
Abstract : Precipitation is a key climate parameter of vegetation and ecosystems in the Iberian Peninsula. Here, we use a regional pollen–climate calibration model and fossil pollen data from eight sites from the Atlantic coast to southern Spain to provide quantitative reconstructions of annual precipitation trends and excursions and their regional patterns for the last 11 700 years. The Early Holocene (11 700 to 11 000 cal. a BP) was characterized by high precipitation values followed by a slowly declining trend until about 9000 cal. a BP in the south and about 8000 cal. a BP in the north. From 8000 to 6000 cal. a BP the reconstructed precipitation values are the highest in most records, especially in those located in the Mediterranean climatic region in the southern part of the peninsula, with maximum values nearly 100% higher than the modern reconstructed values. The results suggest a declining precipitation during the Late Holocene in the south, with a positive excursion at around 2500 cal. a BP, while in the north precipitation remained high until 500 cal. a BP. However, the Late Holocene climate reconstructions in the Iberian Peninsula are biased by intensifying human impact on vegetation. The statistical time series analyses using SiZer technique do not indicate any statistically significant high‐frequency drought events in the region. In general, our results suggest regional differences in the precipitation patterns between the northern and southern parts of the peninsula, with a more distinct Middle Holocene period of high humidity in the south.